Fecundity and egg size of Bali Sardinella Sardinella lemuru (Bleeker, 1853) Off Bulan, Sorsogon. - Kwon, Jiye
The reproductive potential of Bali Sardinella Sardinella lemuru was determined by evaluating both egg quantity and quality. The bali sardines were sampled off Bulan, Sorsogon, Philippines from the month of October to December 2016. Egg quantity was determined by obtaining total and batch fecundity. Total fecundity was determined using gravimetric method and batch fecundity using gravimetric ? hydrated oocyte method. The egg quality was assessed by measuring the oocyte diameter using ImageJ public domain software. The fecundity and egg sizes were both correlated with maternal phenotypes ? standard length, gonad weight and body weight; using both linear and exponential regression models and ANOVA. Results showed a significant positive correation for all total fecundity, batch fecundity and egg sizes with fish length and weight. When two models were compared, total fecundity showed a better fit for linear model while batch fecundity showed a better fit for exponential regression model suggesting a possible threshold. Egg diameter also showed a positive linear correlation and was found that oocytes of S. lemuru become larger as yolky eggs mature to the hydrated stage approaching its spawning stage. The data provided in the study suggest heavy exploitation in some fishing grounds where S. lemuru appears to mature early and at a smaller standard length.